Modified aluminum oxide with high hydroxyl density surface as well as preparation method and application of modified aluminum oxide
By adding isoelectric point regulators and performing surface treatment during the alumina preparation process, the hydroxyl density on the surface of the alumina support is significantly improved, and the lack of hydroxyl density adjustment in the prior art is solved, thereby achieving efficient loading of the catalyst support and adaptation of the heterogeneous catalytic system.
Patent Information
- Application Number
- CN202311114679.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-08-31
AI Technical Summary
The existing surface modification technology of alumina carrier has limited breadth and depth of hydroxyl density adjustment, and often requires the use of surfactants and organic ligands. The steps are cumbersome, the cost is high, and the environmental protection is poor, so it cannot be prepared on a large scale.
Isoelectric point regulators are added during the preparation of alumina, and the hydroxyl group density on the surface of the alumina support is significantly improved through specific surface treatment methods.
The hydroxyl density on the surface of the alumina support has been achieved, which is suitable for catalyst support, improves the load capacity of metal components, and is adapted to different types of heterophase catalytic systems.
Smart Images

Figure CN119551697A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of aluminum oxide materials, and in particular relates to modified aluminum oxide with a high hydroxyl density surface, a preparation method and application thereof. Background Art
[0002] Alumina has excellent thermal stability, corrosion resistance, wear resistance, low cost and other characteristics. It is widely used in the field of chemical catalysis as a carrier of supported metal catalysts and has always been one of the research hotspots. Studies have found that in addition to the active components and additives composition and preparation methods, the activity, selectivity and stability of the catalyst are also closely related to the surface properties and preparation methods of the carrier. Therefore, it is a very effective method to modify the surface of the alumina carrier to better adapt to different process conditions and achieve excellent catalytic performance.
[0003] Patent CN111068750A discloses a surface-modified alumina carrier, a preparation method thereof, and a hydrogenation refining catalyst. The surface-modified alumina carrier is obtained by uniformly mixing pseudo-boehmite precursor slurry, mesoporous molecular sieve, graphene, and organic alcohol, adding a silane coupling agent, adjusting the pH value, aging, filtering and dehydrating, then adding an organic amine and a silane coupling agent to knead into a plastic body, and finally forming, drying, and calcining.
[0004] Patent CN115957821A discloses a γ-alumina carrier and a preparation method thereof. A crown ether organic long chain and a soluble lanthanum salt are hydrothermally reacted to form a crown ether-lanthanum organic ligand, which is uniformly grafted onto the surface of the γ-alumina pores to modify the structure and protect the surface hydroxyl groups, thereby reducing the damage of high temperature to the microporous structure and inhibiting the sintering and phase change of γ-alumina under high temperature environmental conditions.
[0005] Patent CN106732692A discloses a method for preparing a modified alumina carrier, which comprises dispersing, refining and homogenizing a slurry containing a surfactant, a modification aid phosphorus and a magnesium precursor, adding pseudo-boehmite and a nitric acid solution, and mixing and kneading the mixture to form a plastic, and then molding, drying and calcining the plastic to finally obtain a phosphorus and magnesium modified alumina carrier.
[0006] The above inventions are limited in the breadth and depth of the modulation of the surface properties of aluminum oxide, and generally require the use of organic substances such as surfactants and organic ligands, which are cumbersome, costly, and environmentally friendly, and cannot be prepared on a large scale. Summary of the invention
[0007] In order to improve the deficiencies in the prior art, the present invention provides a modified alumina with a high hydroxyl density surface. In the present invention, an appropriate amount of isoelectric point regulator is added during the preparation of alumina, and then the surface of the formed alumina carrier is treated in a targeted manner according to the added isoelectric point regulator, thereby significantly improving the hydroxyl group density on the surface of the alumina carrier.
[0008] One of the purposes of the present invention is to provide a modified alumina having a high hydroxyl density surface, wherein the density of hydroxyl groups on the surface of the modified alumina is 5.1 to 20 mmol / m 2 , preferably 5.5 to 16 mmol / m 2 .
[0009] According to the present invention, the average pore size of the modified alumina is 40 to 250 nm, the most probable pore size is 70 to 400 nm, and the specific surface area is 1 to 120 m 2 / g, bulk density is 0.2-2.0g / ml; preferably, the average pore size of the modified alumina is 50-200nm, the most probable pore size is 100-350nm, and the specific surface area is 3-100m 2 / g, bulk density is 0.3~1.2g / ml.
[0010] According to the present invention, the mass percentage of aluminum oxide in the modified aluminum oxide is 75-99.5%, preferably 85-98%. In addition to aluminum oxide, the modified aluminum oxide also contains other oxide components, for example, at least one of tungsten trioxide, vanadium pentoxide, antimony pentoxide, silicon oxide, zirconium oxide, manganese oxide, tin oxide, titanium oxide, cerium oxide, nickel oxide, copper oxide, zinc oxide, lanthanum oxide, gallium oxide, and indium oxide.
[0011] The modified alumina with a high hydroxyl density surface provided by the present invention is prepared by adding an isoelectric point regulator to a component containing an alumina precursor compound, and then subjected to surface treatment, wherein the alumina precursor compound comprises an aluminum source, a molding agent, a pore expanding agent, a crosslinking agent, and the like.
[0012] The second object of the present invention is to provide a method for preparing the modified alumina having a high hydroxyl density surface, comprising: adding an isoelectric point regulator to a component containing an aluminum source, and obtaining the modified alumina having a high hydroxyl density surface after drying, calcining, and surface treatment. Specifically, the preparation method comprises the following steps:
[0013] (1) mixing components including an aluminum source, a forming agent, a pore expanding agent, an isoelectric point regulating agent, and a crosslinking agent solution to obtain a mixture;
[0014] (2) kneading the mixture obtained in step (1) into a mold, extruding and pelletizing, drying, and calcining to obtain a modified alumina precursor;
[0015] (3) Surface-treating the modified alumina precursor obtained in step (2) to obtain the modified alumina having a surface with a high hydroxyl density.
[0016] According to the present invention, in the method for preparing the modified alumina:
[0017] The aluminum source may be an aluminum source compound commonly used in the art, for example, the aluminum source is selected from at least one of boehmite, pseudo-boehmite, alumina, and aluminum hydroxide, wherein the alumina may be an alumina material commonly used in the art, for example, the alumina may be one or more of γ-alumina, α-alumina, and θ-alumina;
[0018] The molding agent is selected from at least one of starch, methyl cellulose, carboxymethyl cellulose, ethyl cellulose and hydroxyethyl cellulose;
[0019] The pore-enlarging agent is selected from at least one of sesbania powder, polyvinyl alcohol, polyethylene glycol, polyacrylamide, and polypropylene glycol;
[0020] The isoelectric point regulator is selected from at least one of oxides having an isoelectric point of less than 6.5 or greater than 8.5. Preferably, the isoelectric point regulator having an isoelectric point of less than 6.5 is selected from at least one of tungsten trioxide, vanadium pentoxide, antimony pentoxide, silicon oxide, zirconium oxide, manganese oxide, tin oxide, and titanium oxide; and / or, the isoelectric point regulator having an isoelectric point of greater than 8.5 is selected from at least one of cerium oxide, nickel oxide, copper oxide, zinc oxide, lanthanum oxide, gallium oxide, and indium oxide;
[0021] The crosslinking agent in the crosslinking agent solution is selected from at least one of an inorganic acid and an organic acid, preferably at least one of nitric acid, sulfuric acid, hydrochloric acid, formic acid, acetic acid, citric acid, oxalic acid, ascorbic acid, and salicylic acid;
[0022] The solvent in the crosslinker solution is selected from at least one of water and an organic solvent, preferably at least one of water, methanol and ethanol.
[0023] According to the present invention, in the method for preparing the modified alumina:
[0024] Based on the total weight of the aluminum source, the forming agent, the pore expanding agent, and the isoelectric point regulating agent as 100%, the amount of the forming agent is 0.1-10%, the amount of the pore expanding agent is 0.1-10%, and the amount of the isoelectric point regulating agent is 0.01-20%; preferably, based on the total weight of the aluminum source, the forming agent, the pore expanding agent, and the isoelectric point regulating agent as 100%, the amount of the forming agent is 0.5-8%, the amount of the pore expanding agent is 0.5-8%, and the amount of the isoelectric point regulating agent is 0.05-15%;
[0025] Based on 100 g of the aluminum source, the amount of the crosslinking agent solution is 50 to 180 mL, preferably 70 to 160 mL;
[0026] The concentration of the crosslinking agent solution can be adjusted within a wide range. For example, the molar concentration of the crosslinking agent solution is 0.001 to 10 mol / L, preferably 0.01 to 6 mol / L.
[0027] According to the present invention, in step (2) of the method for preparing modified alumina:
[0028] The drying process is not particularly limited, and the drying equipment and drying conditions commonly used in the art can be used to dry the extruded pelletized material;
[0029] The calcination process may adopt calcination equipment and calcination process commonly used in the art. For example, the calcination conditions are: calcination at 350-1200° C. for 1-10 h, preferably, calcination at 500-1150° C. for 2-8 h.
[0030] According to the present invention, in step (3) of the method for preparing modified alumina:
[0031] In step (3), the surface treatment is selected from at least two of acidification or alkalization, crystallization, and irradiation. Preferably, when the isoelectric point regulator is an oxide with an isoelectric point of less than 6.5 and acidification is used, the pH of the acidification treatment needs to be 0.1 to 2 higher than the isoelectric point value of the isoelectric point regulator, preferably 0.2 to 1 higher; when the isoelectric point of the isoelectric point regulator is higher than 8.5, the acidification treatment is not used; when the isoelectric point regulator is an oxide with an isoelectric point greater than 8.5 and alkalization is used, the pH of the alkalization treatment needs to be 0.1 to 4 higher than the isoelectric point value of the isoelectric point regulator, preferably 0.3 to 3 higher;
[0032] Wherein, the acidification conditions are: the acidifier in the acidifier solution is selected from at least one of nitric acid, sulfuric acid, hydrochloric acid, and ascorbic acid; and / or, hydrogen peroxide and / or potassium permanganate are optionally added to the acidifier solution, the acidification temperature is 30-80° C., and the acidification time is 0.1-8 hours; preferably, the concentration of the acidifier in the acidifier solution is 0.001-5 mol / L, the acidification temperature is 35-75° C., and the acidification time is 0.5-6 hours; acidification can generate a large potential difference between the alumina carrier and the surface of the isoelectric point regulator with an isoelectric point of less than 6.5, which is conducive to the fixation of high-mobility hydroxyl groups on the carrier surface;
[0033] The alkalization conditions are as follows: the alkalizer in the alkalizer solution is selected from at least one of sodium hydroxide, sodium bicarbonate, sodium carbonate, potassium hydroxide, potassium bicarbonate, and potassium carbonate, the alkalization temperature is 30-80°C, and the alkalization time is 0.5-8h; preferably, the concentration of the alkalizer in the alkalizer solution is 0.005-5 mol / L, the alkalization temperature is 30-75°C, and the alkalization time is 1-6h; alkalization can generate a large potential difference between the alumina carrier and the surface of the isoelectric point regulator with an isoelectric point greater than 8.5, which is conducive to the fixation of high-mobility hydroxyl groups on the carrier surface;
[0034] The crystallization conditions are as follows: the solvent used for crystallization is at least one of water, methanol, and ethanol; the crystallization atmosphere is at least one of air, argon, and nitrogen; the crystallization temperature is 120 to 250° C.; and the crystallization time is 0.5 to 18 hours. Crystallization can make the hydroxyl groups of the solvent more active, forming a high-density, high-flow hydroxyl region and generating a strong interaction with the carrier surface.
[0035] The irradiation conditions are as follows: the irradiation source is γ-ray, the irradiation dose rate is 0.01-50 kGy / min, and the irradiation time is 0.2-16 h; preferably, the irradiation source is γ-ray, the irradiation dose rate is 0.1-25 kGy / min, and the irradiation time is 0.2-12 h; irradiation can rapidly ionize free water and bound water on the surface of the alumina carrier to generate a large number of active hydroxyl groups;
[0036] The modified alumina obtained after the surface treatment in step (3) needs to be dried. The drying process is not particularly limited and the commonly used drying equipment and drying conditions in the art can be used as long as the modified alumina after the surface treatment can be dried.
[0037] In the present invention, an isoelectric point regulator is added to regulate the potential of local sites on the surface of the alumina carrier, and then combined with a specific surface treatment method, a large number of hydroxyl groups generated on the surface of the alumina are captured or anchored during diffusion and transfer, thereby forming a high-density, highly dispersed hydroxyl area on the surface.
[0038] The third object of the present invention is to provide a modified alumina having a high hydroxyl density surface or a modified alumina having a high hydroxyl density surface obtained by the above preparation method, and use it in a catalyst carrier.
[0039] The present invention provides a modified alumina with a high hydroxyl density surface. By adding an isoelectric point regulator and adopting a corresponding surface treatment method, the hydroxyl group density on the surface of the alumina carrier can be greatly increased, which is beneficial to the loading of metal components in the catalyst. Moreover, the present invention can finely control the hydroxyl group density on the surface of the alumina carrier through the combination of formula and preparation method and the change of process parameters, thereby adapting to different types of multiphase catalytic systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figures 1 to 18 The XRD spectra of aluminum oxide prepared in Examples 1 to 10 and Comparative Examples 1 to 8 are respectively shown. DETAILED DESCRIPTION
[0041] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0042] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0043] Example 1
[0044] Prepare 90 ml of 0.08 mol / L sulfuric acid aqueous solution, add to a mixture of 100 g of boehmite powder, 6 g of carboxymethyl cellulose, 4 g of polyvinyl alcohol and 3 g of vanadium pentoxide (isoelectric point of 1.3), put into a kneader and knead to form a plastic semi-solid, then extrude into a column with an outer diameter of 1 mm and a length of 4 mm, dry at 120°C for 6 h, calcine at 1180°C for 6 h, and then crystallize the column at 130°C in an air atmosphere of 150 ml of methanol for 0.8 h, finally acidify with 30°C, 100 ml, pH 1.8 sulfuric acid solution (the difference between the solution pH and the isoelectric point value of the isoelectric point regulator is 0.5) for 0.6 h, and dry at 120°C for 6 h to obtain the target carrier A1.
[0045] Example 2
[0046] Prepare 125 ml of 0.25 mol / L nitric acid aqueous solution, add to a mixture of 100 g of pseudo-boehmite powder, 8 g of methyl cellulose, 6 g of sesbania powder and 5 g of tungsten trioxide (isoelectric point of 0.4), put into a kneader and knead to form a plastic semi-solid, then extrude into a column with an outer diameter of 1 mm and a length of 4 mm, dry at 120° C. for 6 h, and calcine at 1180° C. for 6 h. Then, crystallize the column at 180° C. for 2 h in 150 ml of water, argon and nitrogen atmosphere (volume ratio of 0.5:1), finally acidify with 40° C., 100 ml, pH 1.3 ascorbic acid solution (the difference between the solution pH and the isoelectric point value of the isoelectric point regulator is 0.9) for 1.5 h, and dry at 120° C. for 6 h to obtain the target carrier A2.
[0047] Example 3
[0048] Prepare 125 ml of an aqueous solution of 0.015 mol / L nitric acid and 0.1 mol / L oxalic acid, add to a mixture of 40 g of aluminum hydroxide powder, 55 g of γ-alumina powder, 5 g of ethyl fiber, 3 g of polyethylene glycol, 5 g of polypropylene glycol and 8 g of silicon oxide (isoelectric point of 2.5), put into a kneader and knead to form a plastic semi-solid, then extrude into a column with an outer diameter of 1 mm and a length of 4 mm, dry at 120° C. for 6 h, and calcine at 1180° C. for 6 h. Then, the column is acidified for 0.6 h with a mixed aqueous solution of 100 ml of hydrochloric acid and hydrogen peroxide at a pH of 2.8 at 40° C. (the difference between the solution pH and the isoelectric point value of the isoelectric point regulator is 0.3), and finally crystallized at 150° C. for 2 h in an argon atmosphere of 150 ml of a 20 wt% ethanol aqueous solution, and dried at 120° C. for 6 h to obtain the target carrier A3.
[0049] Example 4
[0050] Prepare 125 ml of an aqueous solution of 0.015 mol / L nitric acid, 0.1 mol / L oxalic acid and 0.05 mol / L citric acid, add to a mixture of 40 g of aluminum hydroxide powder, 55 g of γ-alumina powder, 5 g of ethyl fiber, 3 g of polyethylene glycol, 5 g of polypropylene glycol and 8 g of antimony pentoxide (isoelectric point of 2) and 8 g of silicon oxide (isoelectric point of 2.2), put into a kneader and knead to form a plastic semisolid, then extrude into a column with an outer diameter of 1 mm and a length of 4 mm, dry at 120°C for 6 h, calcine at 1080°C for 6 h, and then irradiate the column with γ rays at a irradiation dose rate of 2 kGy / min for 5 h, finally crystallize at 150°C in a nitrogen atmosphere of 150 ml of ethanol for 2 h, and dry at 120°C for 6 h to obtain the target carrier A4.
[0051] Example 5
[0052] Prepare 125 ml of an aqueous solution of 0.015 mol / L nitric acid and 0.05 mol / L citric acid, add to a mixture of 40 g of aluminum hydroxide powder, 55 g of γ-alumina powder, 5 g of ethyl fiber, 3 g of polyethylene glycol, 5 g of polypropylene glycol and 10 g of zirconium oxide (isoelectric point of 6), put into a kneader and knead to form a plastic semi-solid, then extrude into a column with an outer diameter of 1 mm and a length of 4 mm, dry at 120°C for 6 h, calcine at 1180°C for 6 h, and then alkalize the column with 60°C, 100 ml, 0.01 mol / L potassium carbonate aqueous solution for 4 h, finally irradiate with γ rays at an irradiation dose rate of 0.5 kGy / min for 12 h, and dry at 120°C for 6 h to obtain the target carrier A5.
[0053] Example 6
[0054] Prepare 125 ml of an aqueous solution of 0.015 mol / L nitric acid, 0.1 mol / L oxalic acid and 0.05 mol / L salicylic acid, add it to a mixture of 40 g aluminum hydroxide powder, 55 g γ-alumina powder, 5 g ethyl cellulose, 3 g polyethylene glycol, 5 g polypropylene glycol and 10 g antimony pentoxide (isoelectric point 2), put it into a kneader and knead it to form a plastic semi-solid, then extrude it into a column with an outer diameter of 1 mm and a length of 4 mm, dry it at 120°C for 6 h, The column was calcined at 1180°C for 6h, and then irradiated with gamma rays at a dose rate of 2kGy / min for 4h, and crystallized at 150°C for 2h in an atmosphere of 200ml 50% ethanol aqueous solution in air and nitrogen (volume ratio 1:1), and finally acidified at 40°C, 100ml, pH 2.2 aqueous nitric acid solution (the difference between the solution pH and the isoelectric point value of the isoelectric point regulator is 0.2) for 5h, and dried at 120°C for 6h to obtain the target carrier A6.
[0055] Example 7
[0056] Prepare 125 ml of 0.25 mol / L nitric acid aqueous solution, add to a mixture of 100 g of pseudo-boehmite powder, 8 g of methyl cellulose, 6 g of sesbania powder and 6 g of lanthanum oxide (isoelectric point of 10), put into a kneader and knead to form a plastic semi-solid, then extrude into a column with an outer diameter of 1 mm and a length of 4 mm, dry at 120°C for 6 h, calcine at 1200°C for 6 h, and then crystallize the column at 160°C in 150 ml of water and air atmosphere for 2 h, finally alkalize with 40°C, 100 ml, pH 11 sodium hydroxide solution (the difference between the solution pH and the isoelectric point value of the isoelectric point regulator is 1) for 1.5 h, and dry at 120°C for 6 h to obtain the target carrier A7.
[0057] Example 8
[0058] Prepare 125 ml of 1 mol / L nitric acid aqueous solution, add it to a mixture of 50 g of pseudo-boehmite powder, 50 g of boehmite powder, 8 g of methyl cellulose, 6 g of sesbania powder, 4 g of zinc oxide (isoelectric point of 9.0) and 4 g of copper oxide (isoelectric point of 9.3), put it into a kneader and knead it to form a plastic semi-solid, then extrude it into a column with an outer diameter of 1 mm and a length of 4 mm, dry it at 120°C for 6 h, roast it at 1230°C for 6 h, and then irradiate the column with gamma rays at an irradiation dose rate of 0.5 kGy / min for 3 h, then put the column in 150 ml of water, and finally alkalize it with 40°C, 0.5 mol / L, 100 ml of potassium bicarbonate, pH of 9.8 for 3 h (the difference between the solution pH and the isoelectric point value of the isoelectric point regulator is 0.8), and dry it at 120°C for 6 h to obtain the target carrier A8.
[0059] Example 9
[0060] Prepare 125 ml of 0.5 mol / L hydrochloric acid aqueous solution, add it to a mixture of 60 g γ-alumina powder, 40 g θ-alumina powder, 6 g hydroxyethyl cellulose, 10 g polyacrylamide, 6 g lanthanum oxide (isoelectric point of 10.0) and 5 g nickel oxide (isoelectric point of 10.5), put it into a kneader and knead it to form a plastic semi-solid, then extrude it into a column with an outer diameter of 1 mm and a length of 4 mm, dry it at 120°C for 6 h, calcine it at 1060°C for 6 h, and then irradiate the column with γ rays at a dose rate of 0.8 kGy / min for 4 h, finally crystallize it at 180°C for 5 h in 150 ml of water, argon and nitrogen (volume ratio 0.3:1), and dry it at 120°C for 6 h to obtain the target carrier A9.
[0061] Example 10
[0062] Prepare 125 ml of an aqueous solution of 0.25 mol / L hydrochloric acid, 0.25 mol / L nitric acid and 0.25 citric acid, add it to a mixture of 60 g of boehmite powder, 20 g of γ-alumina powder, 20 g of α-alumina powder, 4 g of methyl cellulose, 4 g of ethyl cellulose, 5 g of sesbania powder, 3 g of polypropylene glycol, 3 g of gallium oxide (isoelectric point of 9.3) and 3 g of indium oxide (isoelectric point of 8.8), put it into a kneader and knead it to form a plastic semi-solid , and then extruded into columns with an outer diameter of 1 mm and a length of 4 mm, dried at 120°C for 6 h, calcined at 1180°C for 6 h, crystallized at 180°C for 4 h in 150 ml of water and nitrogen atmosphere, and then alkalized at 30°C, 100 ml of a mixed solution of potassium carbonate and sodium carbonate with a pH of 11.9 for 3 h, and finally irradiated with γ rays at a dose rate of 0.8 kGy / min for 4 h, and dried at 120°C for 6 h to obtain the target carrier A10.
[0063] Comparative Example 1
[0064] Prepare 90 ml of 0.08 mol / L sulfuric acid aqueous solution, add to a mixture of 100 g of boehmite powder, 6 g of carboxymethyl cellulose and 4 g of polyvinyl alcohol, put into a kneader and knead to form a plastic semisolid, then extrude and mold into a column with an outer diameter of 1 mm and a length of 4 mm, dry at 120°C for 6 h, calcine at 1180°C for 6 h, and dry at 120°C for 6 h to obtain carrier B1.
[0065] Comparative Example 2
[0066] Prepare 125 ml of 0.25 mol / L sulfuric acid aqueous solution, add to a mixture of 100 g of boehmite powder, 6 g of carboxymethyl cellulose, 4 g of polyvinyl alcohol and 3 g of vanadium pentoxide (isoelectric point of 1.3), put into a kneader and knead to form a plastic semisolid, then extrude into a column with an outer diameter of 1 mm and a length of 4 mm, dry at 120°C for 6 h, calcine at 1180°C for 6 h, and dry at 120°C for 6 h to obtain a modified carrier B2.
[0067] Comparative Example 3
[0068] Prepare 125 ml of 0.25 mol / L sulfuric acid aqueous solution, add to a mixture of 100 g of boehmite powder, 6 g of carboxymethyl cellulose and 4 g of polyvinyl alcohol, put into a kneader and knead to form a plastic semi-solid, then extrude into a column with an outer diameter of 1 mm and a length of 4 mm, dry at 120°C for 6 h, calcine at 1180°C for 6 h, then crystallize the column at 180°C in an argon and nitrogen atmosphere of 150 ml of aqueous solution (volume ratio of 0.5:1) for 2 h, finally acidify with 40°C, 0.8 mol / L, 100 ml of ascorbic acid solution for 1.5 h, and dry at 120°C for 6 h to obtain carrier B3.
[0069] Comparative Example 4
[0070] Prepare 125 ml of 0.25 mol / L sulfuric acid aqueous solution, add to a mixture of 100 g of boehmite powder, 8 g of methyl cellulose, 6 g of sesbania powder and 5 g of tungsten trioxide (isoelectric point of 0.4), put into a kneader and knead to form a plastic semisolid, then extrude into a column with an outer diameter of 1 mm and a length of 4 mm, dry at 120°C for 6 h, calcine at 1180°C for 6 h, crystallize at 150°C in an argon atmosphere of 20 wt% ethanol aqueous solution for 2 h, and dry at 120°C for 6 h to obtain carrier B4.
[0071] Comparative Example 5
[0072] Prepare 125 ml of an aqueous solution of 0.015 mol / L nitric acid and 0.1 mol / L oxalic acid, add to a mixture of 40 g of aluminum hydroxide powder, 55 g of γ-alumina powder, 5 g of ethyl fiber, 3 g of polyethylene glycol, 5 g of polypropylene glycol and 8 g of silicon oxide (isoelectric point of 2.5), put into a kneader and knead to form a plastic semisolid, then extrude into a column with an outer diameter of 1 mm and a length of 4 mm, dry at 120°C for 6 h, calcine at 1180°C for 6 h, then acidify the column with an aqueous solution of 40°C, 100 ml of 0.0015 mol / L hydrochloric acid and 0.001 mol / L hydrogen peroxide for 0.6 h, and dry at 120°C for 6 h to obtain carrier B5.
[0073] Comparative Example 6
[0074] Prepare 125 ml of an aqueous solution of 0.015 mol / L nitric acid and 0.05 mol / L citric acid, add to a mixture of 40 g of aluminum hydroxide powder, 55 g of γ-alumina powder, 5 g of ethyl fiber, 3 g of polyethylene glycol and 5 g of polypropylene glycol, put into a kneader and knead to form a plastic semisolid, then extrude into a column with an outer diameter of 1 mm and a length of 4 mm, dry at 120°C for 6 h, calcine at 1180°C for 6 h, then alkalize the column with 60°C, 100 ml of 0.01 mol / L potassium carbonate aqueous solution for 4 h, finally irradiate with γ rays at a dose rate of 0.5 kGy / min for 12 h, and dry at 120°C for 6 h to obtain the carrier B6.
[0075] Comparative Example 7
[0076] Prepare 125 ml of an aqueous solution of 0.25 mol / L hydrochloric acid, 0.25 mol / L nitric acid and 0.25 citric acid, add to a mixture of 60 g of boehmite powder, 20 g of γ-alumina powder, 20 g of α-alumina powder, 4 g of methyl cellulose, 4 g of ethyl cellulose, 5 g of sesbania powder, 3 g of polypropylene glycol, 3 g of gallium oxide (isoelectric point of 9.3) and 3 g of indium oxide (isoelectric point of 8.8), put into a kneader and knead to form a plastic semisolid, then extrude into a column with an outer diameter of 1 mm and a length of 4 mm, dry at 120°C for 6 h, and calcine at 1180°C for 6 h to obtain carrier B7.
[0077] Comparative Example 8
[0078] Prepare 125 ml of an aqueous solution of 0.015 mol / L nitric acid, 0.1 mol / L oxalic acid, and 0.05 mol / L citric acid, add to 40 g of aluminum hydroxide powder, 55 g of γ-alumina powder, 5 g of ethyl fiber, 3 g of polyethylene glycol, 5 g of polypropylene glycol, and 8 g of chromium trioxide (isoelectric point of 7), put into a kneader and knead to form a plastic semisolid, then extrude into a column with an outer diameter of 1 mm and a length of 4 mm, dry at 120°C for 6 h, calcine at 1080°C for 6 h, and then irradiate the column with γ rays at a dose rate of 2 kGy / min for 5 h, finally crystallize at 150°C in a nitrogen atmosphere of 150 ml of ethanol for 2 h, and dry at 120°C for 6 h to obtain the target carrier B8.
[0079] Test Example 1 Characterization of Physical Properties of Modified Alumina
[0080] The specific surface area of the modified alumina obtained in Examples 1 to 10 and Comparative Examples 1 to 8 was measured by the nitrogen physical adsorption BET method; the bulk density was measured by weighing 50 mL of the carrier mass (taking the arithmetic mean of three measurement results); the pore volume and the most probable pore diameter were measured by the mercury injection method;
[0081] Surface hydroxyl group density measurement method: Weigh 0.1g of modified alumina, put it into a quartz tube, pre-treat it at 450℃ under argon for 0.5h, then start the in-situ hydrogen-deuterium exchange experiment, use a mass spectrometer to record the changes in hydrogen and deuterium signals, and then use the specific surface area and mass normalization to calculate the hydroxyl group density on the carrier surface. The above measurement results are summarized in Table 1.
[0082] Table 1. Physical property test results of modified alumina of Examples 1 to 10 and Comparative Examples 1 to 8
[0083]
[0084] It can be seen from Table 1 that, when the specific surface area, bulk density, average pore size, and most probable pore size are not much different, the method of the present invention can significantly increase the density of hydroxyl groups on the surface of the alumina support. At the same time, by adjusting the type, proportion, isoelectric point regulator, and corresponding surface treatment method (including combination mode, process parameters and conditions, etc.), the density of hydroxyl groups on the surface of the alumina support can be finely controlled.
[0085] Test Example 2 Evaluation of Catalytic Performance of Catalyst Prepared by Modified Alumina
[0086] 50g of modified alumina A1-A10 and B1-B8 were soaked in water for 20 minutes, and the water absorption rate of each carrier was measured after the free water on the surface was drained. Another 50g of the above carrier was taken, and each modified alumina was saturated with a sodium chloropalladate solution containing 0.25g of palladium according to its water absorption rate, dried at 120°C for 4h, and calcined and decomposed at 500°C to obtain catalysts C1-C10 and D1-D8 with a palladium loading of 0.5wt% based on modified alumina A1-A10 and B1-B8, respectively.
[0087] The crystal structures of the catalysts C1-C10 and D1-D8 were detected by X-ray diffractometer. The analysis conditions and parameters were set as follows: the X-ray source was Cu target Kα radiation (CuTarget, Kαradiation, ), scanning range 5°~95°, scanning speed 5°min -1 , step size 0.02°, working voltage 40kV, working current 30mA. The characterization results are listed in Figures 1 to 18 middle.
[0088] from Figures 1 to 18It can be found that in the X-ray diffraction spectra of catalysts C1 to C10 prepared based on modified alumina in Examples 1 to 10, only the characteristic peaks of alumina appear, and no characteristic peaks of palladium or palladium oxide can be observed; in contrast, catalysts D1 to D8 prepared based on modified alumina in Comparative Examples 1 to 8 show a new and obvious characteristic peak of the (100) crystal plane of PdO at around 29°. This shows that, compared with the catalyst prepared using modified alumina as a carrier in the comparative example, the palladium species has a higher dispersion on the surface of the modified alumina as a carrier in the embodiment of the present invention, and its particle size is smaller, the atomic utilization rate of the active components is higher, and the cost of the catalyst can be significantly reduced. This is mainly because the hydroxyl groups with a higher density on the surface of the modified alumina can enhance the interaction between the palladium particles and the alumina carrier, weaken the aggregation and agglomeration tendency of palladium ions under high-temperature decomposition conditions, and maintain the original high dispersion state. Therefore, the modified alumina preparation method provided by the present invention can well meet the various index requirements of various types of supported catalysts for the dispersion form and dispersion degree of different metal active components, and is used to prepare metal-loaded catalysts. The metal can form highly dispersed, small-particle active centers on the surface of the modified alumina carrier, thereby improving the utilization rate of the metal active components.
Claims
1. A modified alumina having a high hydroxyl density surface, wherein the density of hydroxyl groups on the surface of the modified alumina is 5.1 to 20 mmol / m 2 .
2. The modified alumina according to claim 1, characterized in that The density of the hydroxyl groups on the surface of the modified alumina is 5.5 to 16 mmol / m 2 and / or, The average pore size of the modified alumina is 40 to 250 nm, the most probable pore size is 70 to 400 nm, and the specific surface area is 1 to 120 m 2 / g, bulk density is 0.2-2.0g / ml; preferably, the average pore size of the modified alumina is 50-200nm, the most probable pore size is 100-350nm, and the specific surface area is 3-100m 2 / g, bulk density is 0.3~1.2g / ml.
3. The modified alumina according to claim 1, characterized in that In the modified alumina, the mass percentage of alumina is 75 to 99.5%, preferably 85 to 98%.
4. A method for preparing the modified alumina having a high hydroxyl density surface according to any one of claims 1 to 3, comprising: An isoelectric point regulator is added to the components containing an aluminum source, and after drying, calcination and surface treatment, the modified aluminum oxide having a high hydroxyl density surface is obtained.
5. The preparation method according to claim 4, characterized in that: The preparation method specifically comprises the following steps: (1) mixing components including an aluminum source, a forming agent, a pore expanding agent, an isoelectric point regulating agent, and a crosslinking agent solution to obtain a mixture; (2) kneading the mixture obtained in step (1) into a mold, extruding and pelletizing, drying, and calcining to obtain a modified alumina precursor; (3) Surface-treating the modified alumina precursor obtained in step (2) to obtain the modified alumina having a high hydroxyl density surface.
6. The preparation method according to claim 5, characterized in that: The aluminum source is selected from at least one of boehmite, pseudo-boehmite, alumina, and aluminum hydroxide; and / or, The molding agent is selected from at least one of starch, methyl cellulose, carboxymethyl cellulose, ethyl cellulose and hydroxyethyl cellulose; and / or, The pore-enlarging agent is selected from at least one of sesbania powder, polyvinyl alcohol, polyethylene glycol, polyacrylamide, and polypropylene glycol; and / or, The isoelectric point regulator is selected from at least one of oxides having an isoelectric point of less than 6.5 or greater than 8.
5. Preferably, the isoelectric point regulator having an isoelectric point of less than 6.5 is selected from at least one of tungsten trioxide, vanadium pentoxide, antimony pentoxide, silicon oxide, zirconium oxide, manganese oxide, tin oxide, and titanium oxide; and / or, the isoelectric point regulator having an isoelectric point greater than 8.5 is selected from at least one of cerium oxide, nickel oxide, copper oxide, zinc oxide, lanthanum oxide, gallium oxide, and indium oxide; and / or, The crosslinking agent in the crosslinking agent solution is selected from at least one of an inorganic acid and an organic acid, preferably at least one of nitric acid, sulfuric acid, hydrochloric acid, formic acid, acetic acid, citric acid, oxalic acid, ascorbic acid and salicylic acid; and / or, The solvent in the crosslinker solution is selected from at least one of water and an organic solvent, preferably at least one of water, methanol and ethanol.
7. The preparation method according to claim 5, characterized in that: Based on the total weight of the aluminum source, the forming agent, the pore expanding agent, and the isoelectric point regulating agent as 100%, the amount of the forming agent is 0.1-10%, the amount of the pore expanding agent is 0.1-10%, and the amount of the isoelectric point regulating agent is 0.01-20%; preferably, based on the total weight of the aluminum source, the forming agent, the pore expanding agent, and the isoelectric point regulating agent as 100%, the amount of the forming agent is 0.5-8%, the amount of the pore expanding agent is 0.5-8%, and the amount of the isoelectric point regulating agent is 0.05-15%; and / or, Based on 100 g of the aluminum source, the amount of the crosslinking agent solution is 50 to 180 mL, preferably 70 to 160 mL; and / or, The molar concentration of the crosslinking agent solution is 0.001 to 10 mol / L, preferably 0.01 to 6 mol / L.
8. The preparation method according to claim 5, characterized in that: The calcination conditions in step (2) are: calcination at 350-1200° C. for 1-10 h, preferably, calcination at 500-1150° C. for 2-8 h; and / or, In step (3), the surface treatment is selected from at least two of acidification or alkalization, crystallization, and irradiation. Preferably, when the isoelectric point regulator is an oxide with an isoelectric point of less than 6.5 and acidification is used, the pH of the acidification treatment needs to be 0.1 to 2 higher than the isoelectric point value of the isoelectric point regulator, preferably 0.2 to 1 higher; and / or, when the isoelectric point regulator is an oxide with an isoelectric point greater than 8.5 and alkalization is used, the pH of the alkalization treatment needs to be 0.1 to 4 higher than the isoelectric point value of the isoelectric point regulator, preferably 0.3 to 3.5 higher; and / or, The modified alumina obtained after the surface treatment in step (3) needs to be dried.
9. The preparation method according to claim 8, characterized in that: The acidification conditions are: the acidifier in the acidifier solution is selected from at least one of nitric acid, sulfuric acid, hydrochloric acid, and ascorbic acid, and / or hydrogen peroxide and / or potassium permanganate are optionally added to the acidifier solution, and / or the acidification temperature is 30 to 80° C., and / or the acidification time is 0.1 to 8 hours; preferably, the concentration of the acidifier in the acidifier solution is 0.001 to 5 mol / L, and / or the acidification temperature is 35 to 75° C., and / or the acidification time is 0.5 to 6 hours; and / or, The alkalization conditions are: the alkalizer solution uses an alkalizer selected from at least one of sodium hydroxide, sodium bicarbonate, sodium carbonate, potassium hydroxide, potassium bicarbonate, and potassium carbonate, and / or the alkalization temperature is 30-80°C, and / or the alkalization time is 0.5-8h; preferably, the concentration of the alkalizer in the alkalizer solution is 0.005-5mol / L, and / or the alkalization temperature is 30-75°C, and / or the alkalization time is 1-6h; and / or, The crystallization conditions are: the solvent used for crystallization is at least one of water, methanol, and ethanol, and / or the crystallization atmosphere is at least one of air, argon, and nitrogen, and / or the crystallization temperature is 120 to 250° C., and / or the crystallization time is 0.5 to 18 hours; and / or, The irradiation conditions are: the irradiation source is γ rays, and / or the irradiation dose rate is 0.01 to 50 kGy / min, and / or the irradiation time is 0.2 to 16 h; preferably, the irradiation source is γ rays, and / or the irradiation dose rate is 0.1 to 25 kGy / min, and / or the irradiation time is 0.2 to 12 h.
10. Use of the modified alumina having a high hydroxyl density surface according to any one of claims 1 to 3 or the modified alumina having a high hydroxyl density surface obtained by the preparation method according to any one of claims 4 to 9 in a catalyst carrier.
Citation Information
Patent Citations
Preparation method of modified alumina carrier
CN106732692A
Catalyst for preparing isobutene through isobutane dehydrogenation and preparation method thereof
CN105435773A
Preparation method of silicon-containing hydrogenated demetalization catalyst
CN106140181A
Modified alumina carrier, preparation method, hydrogenation catalyst, preparation method and application thereof
CN107511178A
Alumina carrier and preparation method thereof
CN113663699A
Cited By
Hydrogenation catalyst as well as preparation method and application thereof
CN119897101A
A hydrogenation catalyst, its preparation method and use
CN119897101B
Preparation method of molded alumina with high thermal stability
CN120440926A